Hypercoagulation and elevation of blood triglycerides are characteristics of Kawasaki disease. Issue 1 (December 2015) - Chen, Xi; Zhao, Zhen-Wen; Li, Lin; Chen, Xue-Jun; Xu, Hui; Lou, Jin-Tu; Li, Lin-Jie; Du, Li-Zhong; Xie, Chun-Hong
Abstract Background Cardiovascular damages poses risks to children with Kawasaki disease (KD). Although hypertriglyceridemia and hypercholesteremia are risk factors of cardiovascular damages, studies on the blood lipid metabolism in KD are still limited. This study aims to analyze the blood lipids and coagulation in KD. Methods Triglyceride (TG) and cholesterol levels in the plasma and serum from 20 children with KD were examined in comparison with 10 healthy children (HC) as well as 10 children with high fever from identified bacterial infections (BT). Using electrospray ionization mass spectrometry, we profiled the lipid species. Blood coagulation was analyzed. Statistics was analyzed by one-way ANOVA using SigmaStat. Results We found that in KD, plasma TG level was significantly increased, but not serum TG. A total of 19 molecular species of TG were identified, and they were all increased in KD and BT patients, and more pronounced in KD. On the other hand, major molecular species of plasma phosphotidylcholine and lyso-phosphotidylcholine were decreased in KD and BT. Pronounced hypercoagulation was found in KD blood. Conclusion Our data indicate hyperlipidemia in KD, especially for TG, which contributes to the hypercoagulation and the potential risk of cardiovascular damages. Evaluation of blood lipid levels in severe KD patients could provide valuable information for treatment and prognosis, thus would be worthy of consideration.